(untitled) (Connessioni remote. Artivismo_Teatro_Tecnologia, 2021)
In the last century the progress of technology applied to biology, robotics, neuroscience have flowed into the algorithmiclandscape "freeing" spaces of hybridization and contamination. Multimedia arts and new artistic practices have called intoquestion some historical axioms, such as the concept of authorship and uniqueness of the work. An "earlier future" ofcommunication and connection is opening up, increasingly extended and ready to give us a collective imaginationcapable of interpreting epochal changes. Technological art and its experiments have "activated" in the kaleidoscopicgaze of art a performative connective action where art, life and politics are integrated in a "battle" betweendemocratization processes of the network and information and mediated by "liberated" bodies. This is a story of many possible stories, where care fulfills its function in the connection between media and experience amplified by the artisticpractice of a New Living for an ecosystemic culture. The body-device with all its possibilities is disseminated in the network, reinventing the real and the disease and creating "augmented" spaces for criticism, for expression, for action andfor a "ubiquitous salvation". The great opportunity of existence is to express oneself "po(i)etically" through data togenerate an existential debate in culture.